ARTICLE REVIEW: HERBS FOR COMMON COLD TREATMENT - Lifia Bogha Riswanto; Elin Yulinah Sukandar; Atun Qowiyyah (Fakultas MIPA Universitas Garut, 2022)
Herbs have been widely used empirically in preventing and treating diseases, one of which is a common cold. The use of herbs obtained from previous generations that are passed down orally can inhibit its development so that knowledge about traditional medicine needs to be documented and inventoried. This article review aims to examine and find out scientific information on the use of medicinal plants in treating the common cold. The research method used is a literature study obtained both offline and online such as books and original research articles published in SINTA accredited national journals and reputable international journals that have been published in the last 10 years. The results show that from the various plants used empirically, preclinical tests have been carried out. A total of 196 plants have been used empirically to treat the common cold, 5 plants have been tested for expectorant activity, 2 plants have been tested for antitussive activity, 3 plants have been tested for antipyretic activity, 3 plants have been tested for analgesic activity and 1 plant has been tested for anti-allergic activity. From several plants that have been tested for their activity, there are a total of 10 plants that have been tested for their acute toxicity. “Meniran” (Phyllanthus niruri L.) was the best herb to treat the common cold because of having proven to have expectorant, antitussive, analgesic effects and has been tested for acute toxicity test.